O regime jurídico dos empregados das empresas estatais: uma análise à luz do arcabouço normativo-axiológico de direito - Fernandes, Felipe Gonçalves (2023)
As traditionally interpreted by Brazilian doctrine, the bond formed between the Public Administration and its permanent professionals is the legal-administrative one, commonly called “statutory”. However, there are situations in which the entry of personnel into the state environment is allowed under the aegis of other diplomas, such as the Labor Laws. Among these hypotheses, the one referring to employees of stateowned companies stands out. Using this as a premise, the present work focused on the legal regime related to these bonds, but not without first investigating what the employment relationship in the private sector consists of, what are the valid hypotheses of employment in the public sphere, as well as the normative context of the state companies. In a complementary analysis, we conclude that, in the absence of a rational argument, the public entity must submit itself fully to the legal regime of public law. Having established this goal, we analyzed the characteristics of public and private law institutes, from a scientific perspective. In this vein, we point out the existence of classes of institutes specific to each scope: as a rule, the actions of the Public Administration are imputed to the institutes belonging to the classes of public law and those referring to the categories of private law are incumbent on the private people. In addition to this criterion, we identified an axiological component that opposes, imbricatively, the instruments of scope to another, so that any transposition between fields must respect certain rules: either there is an analogous institute, or the institute of a scope must be coupled to the preexisting structure in the other so that it is properly internalized. In this sense, we point out that the use of the term “contract”, in the context of public law, has a different meaning from its homonym in private law. Therefore, when the sign “employment contract” is used in Public Administration, it becomes clear that the meaning of the term will not be the same as that used in the context of a private company. Specifically about state-owned companies, a cut was necessary: in the case of state-owned companies providing public services, the attributable regime will be entirely the administrative legal regime, given the lack of a rational basis for using it privately. On the other hand, in the exploitation of economic activity, public employment contracts are used, which, however, effectively consist of bilateral administrative acts in a private form and labor garment. Thus, we advocate a revision of the links in question in the light of a theory of public law, a proposal that implies a dense review, especially of labor doctrine, when applicable to state-owned companies, whose solutions were pointed out in, order to correct historical hermeneutical misunderstandings and conform them to the normative-axiological framework of the Brazilian State